MENINGKATKAN KEMAMPUAN MEMBACA KATA MELALUI METODE DRILL BAGI ANAK TUNAGRAHITA RINGAN - Nofran - Nofran (Universitas Negeri Padang, 2013)
This research background of the fact that investigators found problems at school SLB Bhakti Amal district. 2x11 Six Lingkung Sicincin, a kid Light Tunagrahita initials SA have difficulty in reading words. Based on this research aims to improve the ability to read words through methods Drill, Drill whether the method can improve the child's ability to read words Tunagrahita. This study used experimental approach in the form of Single Subject Research (SSR) with design A - B. The subjects were children Tunagrahita Class II. Data recorded by the Recording Event procedure checklist marking the number of words read correctly on the student worksheet. Data analysis techniques are used based on the observation data in the form of Visual Analysis of Graphs. The results were analyzed included the number of observations at six times the baseline condition and treatment condition as much as ten times. Thus prove proposed problem formulation, that through Drill method can improve reading skills for children says mild mental retardation in SLB Amal Bhakti Sicincin. Advised the teachers to implement learning by drill method in improving reading skills kids Tunagrahita said.